The EVVA Cohort Study: Anal and Cervical Type-Specific Human Papillomavirus Prevalence, Persistence, and Cytologic Findings in Women Living With HIV. (2nd June 2017) - de Pokomandy, Alexandra; Kaufman, Elaina; de Castro, Christina; Mayrand, Marie-Hélène; Burchell, Ann N; Klein, Marina; Charest, Louise; Auger, Manon; Rodrigues-Coutlée, Sophie; Coutlée, François; ,
Summary: This article presents the first results of the EVVA cohort study: the prevalence of cervical and anal type-specific human papillomavirus (HPV) infection in women living with human immunodeficiency virus (overall and by place of birth), HPV persistence 6 months after baseline, and results of cytologic tests at baseline. Abstract: Background: The risk of anal cancer due to high-risk human papillomavirus (HR-HPV) is higher in women living with human immunodeficiency virus (HIV) than in the general population. We present findings of cervical and anal HPV and cytologic tests at baseline in the EVVA cohort study and HPV persistence data 6 months after baseline. Methods: Semiannual visits included questionnaires, chart reviews, cervical/anal cytologic and cervical/anal HPV testing for 2 years. Genotyping for 36 HPV genotypes was performed using the Roche Linear Array HPV genotyping test. Results: A total of 151 women living with HIV were recruited. At baseline, 75% had anal HPV, 51% had anal HR-HPV, 50% had cervical HPV, and 29% had cervical HR-HPV. Anal HPV-16 and HPV-51 were more frequent in women born in Canada (31% and 29%, respectively, compared with ≤16% for other women). Most anal HR-HPV types detected at 6 months (57%–93%) were persistent from baseline. Findings of anal cytologic tests were abnormal for 37% of women. Conclusions: Anal HPV is highly prevalent in women living with HIV, and type distribution varies by place of birth. High-resolution anoscopy was indicated in more than one third of results. As anal cancer is potentially preventable, these important findings need to be considered when selecting the best approach for anal cancer screening programs.